2020
DOI: 10.1097/md.0000000000020605
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological characteristics of 2019 novel coronavirus diseases (COVID-19) in Jingmen, Hubei, China

Abstract: There is currently a global outbreak of coronavirus disease 2019 (COVID-19), and its epidemic characteristics in the areas where the outbreak has been successfully controlled are rarely reported. Describe the epidemic characteristics of COVID-19 in Jingmen, Hubei, introduce the local prevention and control experience, and observe the impact of various prevention and control measures on the number of new cases. All the COVID-19 patients diagnosed in the municipal districts of Jingmen fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 16 publications
1
21
1
2
Order By: Relevance
“…The relationship between risk of in-hospital mortality and other comorbidities proposed in some series, including high blood pressure [ 29 ], diabetes [ 16 , 20 ], or obesity [ 30 , 31 , 32 , 33 ] were not found in our study. This is in line with the results obtained by two meta-analyses carried out by Wu et al [ 34 ] and Figliozzi et al [ 24 ], which demonstrated that comorbidities and organ dysfunction can aggravate COVID-19, but not directly determine death.…”
Section: Discussioncontrasting
confidence: 74%
“…The relationship between risk of in-hospital mortality and other comorbidities proposed in some series, including high blood pressure [ 29 ], diabetes [ 16 , 20 ], or obesity [ 30 , 31 , 32 , 33 ] were not found in our study. This is in line with the results obtained by two meta-analyses carried out by Wu et al [ 34 ] and Figliozzi et al [ 24 ], which demonstrated that comorbidities and organ dysfunction can aggravate COVID-19, but not directly determine death.…”
Section: Discussioncontrasting
confidence: 74%
“…Until now, there is no directly effective vaccine against the virus and the treatments are mainly symptomatic support therapy, as many antibiotics and antiviral drugs were confirmed ineffective. Even though the COVID-19 virus is highly contagious, according to the latest research, some control methods have proven to be very effective, particularly wearing masks, which could prevent most infections [3], [11], [13], [21], [28], [29], [35], [36], [47].…”
Section: A Characteristics Of the Covid-19 Epidemicmentioning
confidence: 99%
“…Ao analisar a razão de chance entre os óbitos por COVID-19 e as principais comorbidades relatadas pelos pacientes, o Odds Ratio mostrou que pessoas com diabetes têm 8,7 vezes mais chances (OR = 8,7; IC 95% = 6,6;11,4 p < 0,000) de evoluir para óbito; que pessoas com hipertensão têm 7,4 vezes de chance (OR = 7,4; IC 95% = 4,6;11,9 p < 0,000); pessoas com doenças cardiovasculares têm 3,3 vezes de chance (OR = 3,3; IC 95% = 2,4;4,5 p < 0,000); enquanto pessoas com doença respiratória crônica têm 2,0 vezes de chance (OR = 2,0; IC 95% = 1,1;3,7 p < 0,016); e pessoas com asma tem 0,3 vezes de chance (OR = 0,3; IC 95% = 0,1;08 p < 0,009) de ir a óbito (tabela 5). A expansão da COVID-19 se deve, principalmente, às características de disseminação e transmissibilidade do SARS-CoV-2, podendo existir diversos fatores que contribuem para o aumento do número de casos, como os determinantes sociais, culturais e ambientais de cada região 10,11 . Esses fatores intrínsecos de cada região podem explicar o maior número de casos e maior prevalência para as cidades de Santana do Ipanema e Palestina, respectivamente.…”
Section: Análise De Dadosunclassified